Identification and Mapping of Adult Plant Resistance Loci to Leaf Rust and Stripe Rust in Common Wheat Cultivar Kundan - Ren, Y (Plant disease, 2017)
Leaf rust (LR) and stripe rust (YR) are important diseases of wheat worldwide. We used 148 recombinant inbred lines (RIL) from the cross of Avocet × Kundan for determining and mapping the genetic basis of adult plant resistance (APR) loci. The population was phenotyped LR and YR for three seasons in field trials conducted in Mexico and genotyped with the diversity arrays technology sequencing (DArT-Seq) and simple sequence repeat markers. The final genetic map was constructed using 2,937 polymorphic markers with an average distance of 1.29 centimorgans between markers. Inclusive composite interval mapping identified two co-located APR quantitative trait loci (QTL) for LR and YR, two LR QTL, and three YR QTL. The co-located resistance QTL on chromosome 1BL corresponded to the pleiotropic APR gene Lr46/Yr29. QLr.cim-2BL, QYr.cim-2AL, and QYr.cim-5AS could be identified as new resistance loci in this population. Lr46/Yr29 contributed 49.5 to 65.1 and 49.2 to 66.1% of LR and YR variations, respectively. The additive interaction between detected QTL showed that LR severities for RIL combining four QTL ranged between 5.3 and 25.8%, whereas the lowest YR severities were for RIL carrying QTL on chromosomes 1BL + 2AL + 6AL. The high-density DArT-Seq markers across chromosomes can be used in fine mapping of the targeted loci and development SNP markers